2021
DOI: 10.3390/ijms22105081
|View full text |Cite
|
Sign up to set email alerts
|

The Role of GSK-3β in the Regulation of Protein Turnover, Myosin Phenotype, and Oxidative Capacity in Skeletal Muscle under Disuse Conditions

Abstract: Skeletal muscles, being one of the most abundant tissues in the body, are involved in many vital processes, such as locomotion, posture maintenance, respiration, glucose homeostasis, etc. Hence, the maintenance of skeletal muscle mass is crucial for overall health, prevention of various diseases, and contributes to an individual’s quality of life. Prolonged muscle inactivity/disuse (due to limb immobilization, mechanical ventilation, bedrest, spaceflight) represents one of the typical causes, leading to the lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 128 publications
5
32
0
Order By: Relevance
“…Consistent with its role as a negative regulator of muscle size 10 , we found that GSK3 inhibition with tideglusib treatment restored EDL:body mass ratio in D2 mdx mice to levels comparable with WT mice (Fig. 2a).…”
Section: Resultssupporting
confidence: 74%
See 2 more Smart Citations
“…Consistent with its role as a negative regulator of muscle size 10 , we found that GSK3 inhibition with tideglusib treatment restored EDL:body mass ratio in D2 mdx mice to levels comparable with WT mice (Fig. 2a).…”
Section: Resultssupporting
confidence: 74%
“…It is well-established that GSK3 counteracts calcineurin by rephosphorylating NFAT, thereby preventing its nuclear activation and the transcription of its downstream targets 10 . Thus, in addition to its role in regulating muscle mass, we and others have shown that GSK3 negatively regulates the oxidative fiber type, and that its inhibition in muscle can promote the oxidative myogenic program 10,25,42 . Our findings presented here are strongly aligned with this, as we observed a significant increase in the proportion of oxidative (I and IIA) fibers in tideglusib treated vs vehicle treated D2 mdx EDL muscles.…”
Section: Tideglusib Is the Most Clinically Advanced Gsk3 Inhibitor Th...mentioning
confidence: 99%
See 1 more Smart Citation
“…The use of GSK-3β kinase inhibitors during hindlimb unloading in rats led to the prevention of a decrease in the expression of PGC-1α and mitochondrial proteins and the prevention of the slow-to-fast fiber-type transformation [ 201 , 231 ]. In recent years, GSK-3β was shown to play a significant role in the development of changes in postural muscles during variants of muscle unloading; the inhibition of GSK-3 can lead to an increase in the work capacity of skeletal muscles in rodents, which makes GSK-3β inhibitors some of the most promising pharmacological agents as a countermeasure against unloading-induced changes [ 280 , 281 ].…”
Section: Countermeasures To Changes Caused By Reduced Motor Activitymentioning
confidence: 99%
“…Glycogen synthase kinase 3 (GSK-3) is a multifaceted Ser/Thr protein kinase known to phosphorylate several hundred substrates [ 25 ], thereby regulating a wide range of intracellular processes including protein turnover in skeletal muscle [ 26 ]. GSK-3 exists in two isoforms, GSK-3α and GSK-3β, among which GSK-3β is considered to be the most expressed and active isoform within skeletal muscles [ 27 ].…”
Section: Introductionmentioning
confidence: 99%